Telework and its Impacts on Worker's Health (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
The article analyzes the telework regulations established by the Labor Reform (Law No. 13,467/2017) and later amended by Law No. 14,442/2022. The author focuses on the psychosocial and ergonomic risks inherent in this modality, discussing the exclusion from the working hours regime (Art. 62, III of the CLT) and the subsequent right to disconnection. It is argued that flexibility cannot nullify the duty of vigilance and the employer's responsibility for the employee's health, aiming to prevent burnout and other pathologies of contemporary work. (Received: June 2025 | Accepted: September 2025).
Keywords: Telework; Worker's Health; Right to Disconnection; Labor Reform